A Comparative Study of Psycho-social and Socio-economic Issues on Mental Health in Nigeria - Imbur, Moses T. (Practicum Psychologia, 2024)
This study aims to investigate the intricate relationship between psycho-social and socio-economic factors and their impact on mental health in Nigeria. Mental health issues have become increasingly prevalent in Nigeria, yet there is a dearth of comprehensive research exploring the multifaceted influences of psycho-social and socio-economic factors on mental well-being within the Nigerian context. Through a comparative analysis, this research examines the interplay between psychosocial variables such as social support, stigma, and cultural beliefs, alongside socio-economic factors including income, education, and employment status. Utilizing both quantitative and qualitative methodologies, data will be gathered from diverse demographic groups across various regions of Nigeria. The findings from this study will contribute to a deeper understanding of the nuanced dynamics shaping mental health outcomes in Nigeria. Additionally, the results will inform targeted interventions and policies aimed at addressing the complex challenges faced by individuals grappling with mental health issues in the Nigerian society. By bridging the gap between research and practice, this study endeavors to foster holistic approaches to mental health promotion and intervention tailored to the unique socio-cultural context of Nigeria.